Synthesis, characterization, and biological evaluation of coumarin-nitric oxide donor hybrids as anti-tubercular agents - Afeez I. Kareem; Sarel F. Malan; Erika Kapp; Sean Shamido; Jacques Joubert (Elsevier, 2024)
This study presents a series of coumarin nitric oxide donor hybrids that were synthesized, and characterized using FT-IR, H NMR, C NMR, and HR-MS techniques. Initial screening for anti-tubercular activity was conducted against Mycolicibacterium smegmatis MC2155 (M.smeg) under both nutrient-rich and nutrient-poor conditions. Under nutrient-rich conditions, little inhibition was observed. However, four compounds (1e, 2o, 3f, and 5e) demonstrated notable antiproliferative activity under nutrient-poor conditions, with inhibition rates exceeding 95 % at a 50 μM concentration. Subsequent testing of these compounds on Mycobacterium tuberculosis (M.tb) under nutrient-rich conditions showed inhibition rates ranging from 11 % to 37 % at 50 μM. These results indicate that the coumarin nitric oxide donor hybrids are potentially effective in nutrient-limited environments, similar to the intracellular conditions faced by M.tb. In silico cytotoxicity predictions, compared with rifampicin, indicated potentially low toxicity for these compounds. Further optimization and studies are needed to enhance their efficacy under normal conditions, which could lead to the development of new therapeutic strategies against tuberculosis.